An integrative taxonomic approach to the identification of three new New Zealand endemic earthworm species (Acanthodrilidae, Octochaetidae: Oligochaeta) - Boyer, Stephane; Blakemore, Robert J.; Wratten, Steve D. (Zootaxa, 2011)
This work adds three new species to the ca. 200 currently known from New Zealand. In Acanthodrilidae is Maoridrilus felix and in Octochaetidae are Deinodrilus gorgon and Octochaetus kenleei. All three are endemics that often have restricted ranges; however, little is yet known of their distribution, ecology nor conservation status. DNA barcoding was conducted, which is the first time that New Zealand endemic holotypes have been so characterized. The barcoding region COI (cytochrome c oxidase subunit 1) as well as the 16S rDNA region were sequenced using tissue from the holotype specimen to provide indisputable uniqueness of the species. These DNA sequences are publically available on GenBank to allow accurate cross checking to verify the identification of other specimens or even to identify specimens on the basis of their DNA sequences alone. Based on their 16S rDNA sequences, the position of the three newly described species in the phylogeny of New Zealand earthworms was discussed. The description of new species using this approach is encouraged, to provide a user-friendly identification tool for ecologists studying diverse endemic faunas of poorly known earthworm species.